Level and determinants of pharmacovigilance programme awareness in Nigeria: A multilevel analysis (2017)
Previous studies have reported poor awareness of the Pharmacovigilance Programme (PP) among health professionals in Nigeria but similar information on the general population is unavailable. This study was designed to investigate the individual and contextual factors associated with awareness of the PP among the general population. The study utilised data collected in the 2012 National HIV and AIDS and Reproductive Health and Serological Survey which were collected through a multi-stage cluster survey among women aged 15-49 years and men aged 15-64 years across all the states in Nigeria. Data on regulatory activities about food and drugs as well as household and individual characteristics were extracted and analyzed using descriptive statistics and multilevel logistic regression. Mean age of the respondents was 31.45±11.8 years. Females constituted 50.1% while 68.7% resided in rural areas. Only 26.0% of the respondents were aware of the PP and this was significantly higher among those with higher education (57.7%) and those who have seen/heard any campaign on Adverse Drug Reactions (ADRs) (79.7%). Participants who had seen/heard any campaign on ADRs were more likely to be aware of the PP (Odd Ratio [OR]: 32.85, 95% Confidence Interval [CI]: 29.13–36.57). Tertiary education (OR: 4.29, 95% CI: 3.51–5.07), and secondary education (OR= 2.35, 95%C.I= 2.0–2.70) significantly increased PP awareness. Participants who were employed and those who resided in urban communities were more likely to be aware of the PP in Nigeria. Generally, awareness of the PP in Nigeria is low. Awareness campaigns should be re-packaged to reach rural dwellers and those with lower education.